2015
DOI: 10.1037/a0039572
|View full text |Cite
|
Sign up to set email alerts
|

Exploration as a mediator of the relation between the attainment of motor milestones and the development of spatial cognition and spatial language.

Abstract: The embodied-cognition approach views cognition and language as grounded in daily sensorimotor child-environment interactions. Therefore, the attainment of motor milestones is expected to play a role in cognitive-linguistic development. Early attainment of unsupported sitting and independent walking indeed predict better spatial cognition and language at later ages. However, evidence linking these milestones with the development of spatial language and evidence regarding factors that might mediate this relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 74 publications
4
83
0
1
Order By: Relevance
“…The average number of targets identified across three trials was scored. Visuospatial short-term memory was assessed with a memory for location task in which children had to remember the location of hidden toys (Oudgenoeg-Paz, Volman, & Leseman, 2015;Pelphrey et al, 2004;Vicari, Caravale, Carlesimo, Casadei, & Allemand, 2004). Six identical white boxes were used as hiding locations.…”
Section: Cool Executive Functionsmentioning
confidence: 99%
“…The average number of targets identified across three trials was scored. Visuospatial short-term memory was assessed with a memory for location task in which children had to remember the location of hidden toys (Oudgenoeg-Paz, Volman, & Leseman, 2015;Pelphrey et al, 2004;Vicari, Caravale, Carlesimo, Casadei, & Allemand, 2004). Six identical white boxes were used as hiding locations.…”
Section: Cool Executive Functionsmentioning
confidence: 99%
“…The later shift from crawling to walking has been linked to cascading shifts in how infants interact with caregivers, as well as changes in how caregivers in turn respond to their infants (Campos et al, ; Clearfield, ; Karasik, Tamis‐LeMonda, & Adolph, , , ). Finally, it has been shown that infants and toddlers who demonstrate proficiency in a motor skill (i.e., attainment of independent sitting or walking; greater motor control) are more likely to exhibit advanced language skills (Alcock & Krawczyk, ; He, Walle, & Campos, ; Libertus & Violi, ; Oudgenoeg‐Paz, Leseman, & Volman, ; Oudgenoeg‐Paz, Volman, & Leseman, ; Walle, ; Walle & Campos, ; Walle & Warlaumont, ; Wang, Lekhal, Aaro, & Schjolberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier sitting onsets predict better spatial memory at 24 months [29]. Although object exploration at 20 months failed to mediate this e↵ect, exploratory di↵erences earlier in infancy might account for it.…”
Section: Changes In Exploratory Abilities Have Downstream E↵ectsmentioning
confidence: 81%
“…The attainment of sitting, crawling, and walking have downstream e↵ects on object perception [9] and spatial cognition [8,29]. Infants' ability to sit independently facilitates visual-manual exploration of objects [13,14], which, in turn, facilitates object perception [9].…”
Section: Changes In Exploratory Abilities Have Downstream E↵ectsmentioning
confidence: 99%